2010
DOI: 10.1177/1420326x10383472
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Subjective Response for Corrected Colour Temperature Conditions in a Specific Space

Abstract: The luminous environment in a space is one of the key factors affecting the occupants' work performance and mood. An illuminance value is quantitatively standardised and recommended for a specific space, but correlated colour temperature (CCT) is not. Although some studies on CCT conditions have shown that higher CCT conditions appear brighter to people than lower CCT conditions, other studies have indicated that there is no relationship between brightness perception and CCT conditions. This paper reports the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 17 publications
2
44
0
Order By: Relevance
“…Our postulation was that, as respondents felt more co mfortable under CW L, they typed significantly faster than WWL (least co mfortable perceived). The finding was supported by finding fro m another research by Park et al (2010), where their work performance under CW L condition was shown to be higher than WWL.…”
Section: Visual Comfort and Subjective Preferences Assessmentsupporting
confidence: 80%
See 1 more Smart Citation
“…Our postulation was that, as respondents felt more co mfortable under CW L, they typed significantly faster than WWL (least co mfortable perceived). The finding was supported by finding fro m another research by Park et al (2010), where their work performance under CW L condition was shown to be higher than WWL.…”
Section: Visual Comfort and Subjective Preferences Assessmentsupporting
confidence: 80%
“…However, few studies found contradicting conclusion where 3,000K light source was comfo rtable and high CCT (17,000K) lead to dizziness (Park et al, 2010;Gó rnicka, 2008).…”
Section: Visual Comfort and Subjective Preferences Assessmentmentioning
confidence: 99%
“…Such a design may unpremeditatedly help to reveal the influence of other contextual factors on colour preference, since it relatively weakens the impact of light when compared to the conditions where CCT differs. However, unlike colour fidelity, colour preference should not be restricted by a reference light source, since in many cases people actually want to choose a favorite light irrespective of the CCT 4,26,[33][34][35][36][37] . Secondly, the experimental object is also an important concern.…”
Section: Introductionmentioning
confidence: 99%
“…The luminous environment in a space is one of the key factors affecting the occupants’ work performance and mood . Current concerns about sustainability may lead to a reduction in illuminance levels in office light; in the commercial sector, lighting accounts for up to 40% of energy costs in a typical UK office .…”
Section: Learning Productivity and Alertness In Indoor Spacesmentioning
confidence: 99%